2015
DOI: 10.1167/iovs.15-17857
|View full text |Cite
|
Sign up to set email alerts
|

Cobalamin C Deficiency Shows a Rapidly Progressing Maculopathy With Severe Photoreceptor and Ganglion Cell Loss

Abstract: Patients with early-onset cblC and MMACHC mutations showed an early-onset, unusually fast-progressing maculopathy with severe central ONL and GCL loss. An abnormally thickened inner retina supports a remodeling response to both photoreceptor and ganglion cell degeneration and/or an interference with normal development in early-onset cblC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 69 publications
(151 reference statements)
4
30
0
Order By: Relevance
“…Comparisons of total plasma homocysteine, methionine, and methylmalonic acid levels in our cohort versus several large published studies 10,11,1620 demonstrated lower total plasma homocysteine and methylmalonic acid levels in our cohort as compared to these previously published studies (Figures 2a, Figure 2c) whereas methionine levels were comparable (not shown). The high frequency of the c.482G>A(p.Arg161Gln) pathogenic variant in our cohort contributes to this observation as 13/27 (48%) of our individuals are compound heterozygous for this variant compared to 4/86 (5%) individuals in these published studies (combined) 8, 9, 1418 .…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Comparisons of total plasma homocysteine, methionine, and methylmalonic acid levels in our cohort versus several large published studies 10,11,1620 demonstrated lower total plasma homocysteine and methylmalonic acid levels in our cohort as compared to these previously published studies (Figures 2a, Figure 2c) whereas methionine levels were comparable (not shown). The high frequency of the c.482G>A(p.Arg161Gln) pathogenic variant in our cohort contributes to this observation as 13/27 (48%) of our individuals are compound heterozygous for this variant compared to 4/86 (5%) individuals in these published studies (combined) 8, 9, 1418 .…”
Section: Resultssupporting
confidence: 54%
“…One of the observations in this study is that those in our cohort have lower total plasma homocysteine and methylmalonic acid levels compared to several published studies 10,11,1620 . The high frequency of the c.482G>A (p.R161Q) pathogenic variant in this study contributes to this observation.…”
Section: Discussionsupporting
confidence: 50%
“…Neonates typically show lethargy, seizures and muscular hypotonia, often in combination with megaloblastic anaemia or neutropenia/pancytopenia. Up to 50 % of infants exhibit signs of visual impairment such as nystagmus on the background of retinopathy or optic atrophy (Bonafede et al 2015; Weisfeld-Adams et al 2015; Brooks et al 2016). Microangiopathic renal or pulmonary disease mostly manifests early but may also be present in older children or adults (Grangé et al 2015; Kömhoff et al 2013; Sharma et al 2007).…”
Section: Which Clinical Signs Are Characteristic For Remethylation Dementioning
confidence: 99%
“…11,12 The ocular and cognitive manifestations of the disease seem especially difficult to prevent. 5,6,8,1113 The mainstay of treatment includes high-dose intramuscular hydroxycobalamin (OHCbl), which can lower serum MMA and homocysteine levels and increase serum methionine levels. 14,15 Betaine can also be used to increase remethylation of homocysteine to methionine.…”
Section: Introductionmentioning
confidence: 99%